Sistem Informasi Penggajian Karyawan Berbasis Website Pada Sekolah Tunas Bangsa Greenville - Dominggus Jabi; Ratih Yulia Hayuningtyas (LPPM Universitas Bina Sarana Informatika, 2022)
Tunas Bangsa Greenville School is an educational institution under the Harapan Bangsa Foundation and its address is at Jl. Mango West Jakarta. Education at Tunas Bangsa Greenville School starts from nursery, kindergarten, elementary school, junior high school, and high school. Tunas Bangsa Greenville School in processing financial data, especially employee payroll, still carried out by recording in the books. In the payroll recording process carried out at the Tunas Bangsa Greenville School, errors often occur such as inputting data in the ledger so that there is a difference in the calculation of salaries, poor data storage which causes problems with lost and damaged documents, the data search process takes a long time and the preparation of payroll reports is still less efficiency. This problem often creates delays in the payroll and reporting process, to facilitate payroll data processing, access and print reports or salary slips, an effective and efficient payroll information system is needed and integrated with the database. Therefore in this study resulted in a payroll information system using the web that contains employee data, attendance data, overtime data, payroll data to employee salary slips so that they can overcome the problems that exist at the Tunas Bangsa Greenville School.